The Intrinsic Role Of Endoplasmic Reticulum Stress Sensors In The Mechanism Underlying The Depressive Symptoms And Kratom Dependence In Chronic Kratom Users - Fauzi, Nurul Atiqah Muhamad (2023)
Background: This study aimed to determine the differences in the mRNA and protein expression of ER stress sensors (such as BiP, XBP1, ATF4 and CHOP) in the peripheral blood mononuclear cells (PBMCs) between non-drug using healthy controls and regular kratom users, evaluate how alterations of ER stress sensors expression was associated with the kratom use patterns (such as first age of using kratom, kratom use duration, kratom use average daily frequency, kratom use average daily quantity, and time of last kratom use prior to blood collection) and assess the correlations between the mRNA and protein expression of ER stress sensors in the peripheral blood mononuclear cells (PBMCs) among regular kratom users and the severity of depressive symptoms on kratom abstinence and kratom dependence severity. Methods: Data on socio-demographic characteristics were collected from kratom users and healthy controls. While data on kratom use patterns, kratom dependence severity and depressive symptoms on kratom abstinence were collected from kratom users. The expression of mRNA and protein of selected ER stress sensors (such as BiP, XBP1, ATF4 and CHOP) in the PBMCs of kratom users and healthy controls were measured with qRT-PCR and western blot, respectively. Results: A total of 20 kratom users and 20 healthy controls completed the study. The levels of expression of mRNA and protein of BiP were significantly elevated in kratom users compared with healthy controls regardless of the kratom use patterns.